Ionic conductivity of PEMA-LiClO4 polymer electrolytes - Amir, Shahrul; Othman, Raihan; Subban, Ri Hanum Yahaya; Mohamed, Nor Sabirin (Penerbit UKM, 2011)
Solid polymer electrolytes comprised of various weight percent ratios of poly(ethyl methacrylate) (PEMA) and lithium perchlorate (LiClO4) salt were prepared via solution casting technique using N,N-dimethylformamide (DMF) as the solvent. The conductivity values of the electrolytes were determined via impedance spectroscopy. The conductivity of the PEMA-LiClO4 electrolytes increased with increasing salt concentration and the highest conductivity obtained was in the order of 10-6 S cm-1 at salt concentration of 20 wt%. The conductivity decreased for higher salt concentration. In order to understand the conductivity behavior, XRD and dielectric studies were done. The results showed that the conductivity was influenced by the fraction of amorphous region and number of charge carriers in the system. The transference number measurement was also performed on the highest conducting electrolyte systems. The result of the measurement indicated that the systems were ionic conductors.